Fast heating of super-solid density plasmas towards laser fusion ignition - Kodama, R; Tanaka, K; Fujioka, S; Fujita, H; Habara, H; Izawa, Y; Jitsuno, T; Kitagawa, Y; Krushelnick, K; Mima, K; Miyanaga, N; Nagai, K; et al. (2002)
We have studied fast heating of highly compressed plasmas using multi 100 TW laser light. Efficient propagation of the ultra-intense laser light and heating of the imploded plasmas were realized with a cone-attached shell target. Energy deposition rate of the ultra-intense laser pulse into high-density plasmas was evaluated from neutron measurements. Generation and propagation property of energetic electrons in the ultra-intense laser interactions were also investigated with solid density targets. About 40% of the laser energy converted to mega electron volts energetic electrons in the interactions with solid targets at intensities of 1019W cm-2. These electrons propagated in the high-density plasmas with a divergence of 20-30° or jet-like collimation. Taking account of these experimental results, heating laser spot size is optimized for laser fusion ignition with a simple estimation.